Historical survey of new concepts of lifelong learning during aging - Parlić Božović, Jasna Lj.; Parlić Milosavljević, Jelena Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Learning and education gradually occupy an important place in human life.Therefore, continuing socio-political and economic changes, rapid scientific and technological development, the expansion of knowledge, formed the phenomenon of the learning society. Its theoretical basis can be found in the concept of learning in the course of a lifetime, example:permanent learning and education in the aging process. On the other hand, the rapid changes taking place in the world, seeking to know the day is increasing. In the center of a thriving economy and a developed society are knowledge and ability, and education and learning become the instrument that. key socio-economic progress. Nevertheless, shorter working hours and longer life expectancy retirement also increases the amount of time available for other activities. In all areas, there are more opportunities for learning outside the school, and qualifications, in the traditional sense of getting out in front of new trends competence and adaptability. Adults who are constantly in the process of aging, the process of continuing education and learning are significantly different quality in relation to children, therefore it is necessary and a different approach to the children, and a different approach to teaching adults in the era of change, due to life and work experience, educational level, psychological and physical characteristics but also because of their social status. This paper will be an attempt, which will show the theoretical analysis of many aspects of learning, types, shapes, possibilities and limits of learning, the basic needs of adults in the aging process, as well as provide answers to the question why a grown man in the aging process learns who the person in the learning process and learning how to function in a process of aging.